Online Gambling Criminal Act In Criminology Perspective - Ageovani Amanda Putra Damanik; Novelina Mutiara S Hutapea; Desy Kartika C Sitepu (Program Pascasarjana UIN Sumatera Utara, 2023)
The phenomenon of online gambling is increasingly rampant and has become a form of crime that is worrying in Indonesia, as widely reported in national and local media. This study aims to analyze the modus operandi of online gambling, identify obstacles in efforts to overcome it, and evaluate the steps that have been taken by law enforcement officers in eradicating this case. This study uses a document review method with a normative legal approach, which refers to secondary data in the form of laws and regulations, legal theory, and the opinions of relevant experts. The results of the study indicate that the modus operandi of online gambling is carried out through a mechanism for sending funds to admin accounts, which are then converted into game currency. One of the main obstacles in eradicating online gambling is the difficulty of identifying and closing gambling sites that often use misleading names and operate from abroad, where gambling is legal according to the laws of their country of origin. In efforts to overcome it, law enforcement officers are guided by Article 303 bis Paragraph (1) of the Criminal Code as the legal basis for prosecuting online gambling perpetrators. However, the effectiveness of law enforcement still faces various challenges, so a more comprehensive strategy is needed, including strengthening regulations, updating monitoring technology, and increasing digital literacy in the community to prevent involvement in online gambling..